Electrochemical synthesis of graphene/MnO2 in an architecture of bilayer microtubes as micromotors - Ye, H.; Sun, Hongqi; Wang, S. (Elsevier BV, 2017)
Micro/nanomotors (MNMs) that could perform diverse tasks are the most dynamic research areas in nanoscience and nanotechnology. Up to now, the majority of micromotors contain the precious metal platinum (Pt) as the catalyst for propulsion. The high cost and scarcity of Pt seriously impede its practical application. The exploration of manganese oxide based MNMs provides a route to circumstance the drawbacks of Pt. In this paper, graphene/MnO2 microtubes as a highly efficient micromotor was fabricated by a template-assisted electrochemical process. The resulted micromotors show a good motion behavior in a wide range of hydrogen peroxide (H2O2) concentrations. Owing to its robust motion, easy functionalization, a large quantity of surface functional groups for modification, and simple synthesis, these fine micromotors hold a great promise for biomedicine and environmental applications.